Analysis Of Cloud Based Multitenant Load Scaling (International Journal of Engineering and Computer Science, 2018)
: An internet based computing,through which resources are shared to customers .In multinenancy ,customers share same hardware and database .Many clients are working under one server and single instance of application is available to many customers . With minumum resource and cost , requirements can be fulfilled .With the help of scaling , resources can be allocated as per requirements. Increasing the potentiality of system,by adding /removing components or functionality or components of systems van be termed as scalability.